Case Report: Successful Management of Conidiobolus Lamprauges Rhinitis in a Dog - Jaffey, Jared A.; Hostnik, Eric T.; Hoffman, Aline Rodrigues; Jay, Maureen; Ferguson, Sylvia H.; Wiederhold, Nathan P. (Frontiers in Veterinary Science, 2021)
This is a case of Conidiobolus lamprauges rhinitis in a Goldendoodle, that was presented for evaluation of sneezing, coughing, lethargy, as well as right-sided epistaxis and clear ocular discharge. Computed tomography revealed a large amount of soft tissue within the right nasal passage that obscured the osseous turbinates from the right maxillary canine tooth to the right side of the choanae. Biopsies revealed eosinophilic granulomas with variable number of basophilic to negatively staining, septate, fungal hyphae with non-parallel walls and irregular branching that were subsequently determined to be Conidiobolus lamprauges via panfungal PCR and sequencing. Complete and sustained resolution of clinical disease was achieved after 75 days of systemic antifungal therapy. This report describes for the first time, important clinical features of a dog with nasal conidiobolomycosis that will facilitate its recognition, prognostication, and treatment in clinical practice.